THE EFFECT OF DIFFERENT ORGANIC EXTRACTION SOLVENTS ON THE PROFILE OF FATTY ACID IN MUDSKIPPER (Periophthalmodon schlosseri)MEAT - Selpiana Sihombing; Edison Edison; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAK    This study aimed to determine the type and the amount of fatty acids in mudskipper (Periophthalmodon schlosseri)meat by using different organic solvents, as the best organic solvent to extract fatty acids. The study was using the experimental method. The parameters assessed were the yield, proximate composition, fish meat extraction and identification of fatty acid content. The results showed that the yield of fish oil in the fish was 30.0%, the water content (proximate) in fresh meat was 76.52%, ash 0.38%, protein 17.50%, and fat content 0.51%, all calculated in wet bases. The amount of fish oil extracted by using different organic solvents were 4.50 gs, 4.30  and 2.50 gs, by using ethanol, methanol, and isopropanol, respectively. Meanwhile, the amount of fatty acid yielded were 23.50%, 22.63% and 25.76% by using ethanol, methanol, and isopropanol, respectively. Keywords: mudskipper, fish oil, extraction, fatty acid